The Sea Vault: Offshore Ecotourism Aquaculture Centre At Pulau Besar Johor - Ruslan, Alisufian; Yusof, Zeenat Begam (2020)
Malaysia is one of the major fish consumers in the world with 56.5kg of fish were consumed per person each year which is higher than the world average fish consumption; below 20kg per capita (Infofish, 2016). The statistic also indicates that Malaysian consumed fish slightly higher than Japanese. The high fish consumption affected the number of captured fisheries which is decreasing due to overfishing. Malaysia at this point must not solely rely on captured fisheries as the main seafood resource hence aquaculture is the most suitable way to overcome the issue. According to Food and Agriculture Organization of the United Nation (FAO) (2018), Malaysia ranked 15th in the world aquaculture industry and 11th in the marine capture production in 2016. It has been decades since aquaculture implemented in Malaysia with 13.5% increasing rate from 2005-2014 (FAO, 2018). Most of the aquaculture conducted in Malaysia are inland waters where it is more beneficial for inland area to build and develop other development. As for offshore aquaculture mostly on freshwater bodies such as rivers and lakes create an unsustainable aquaculture process which cause water pollution and fish health depletion which lead to the spread of disease. Due to this matter, the idea of providing an offshore ecotourism aquaculture center at the open ocean near Pulau Besar, Johor is to increase the marine fisheries production as well as improve the marine ecosystem. The centre will consist of research facilities for breeding and production process and ecotourism amenities such as accommodation, restaurant and exploration facilities for above and below water experience to spread awareness as well as learning the aquaculture process.